Biochemical Factors associated with Breast Cancer in Bangladeshi Women - Hussain, DAS; Ahmed, S; Hoque, M; Rabbi, SMR; Masood, S; Shafi, T; Parvia, T; Chaudhury, HS (Bangladesh Journal of Medical Biochemistry, 2014)
Breast Cancer is the commonest maligrancy in woment. A study was carried out in the Department of Biochemistry, Dhaka Medical College to investigate some of the biochemical features that are associated with breast cancer occurring in Bangladeshi women. Thirty diagnosed breast cancer patients and thirty healthy women were selected. A questionnaire was used for collecting information regarding age, family history, physical activity and exercise, BMI, diet, smoking, alcohol abuse, addiction, details of menstrual and obstetric history, breast-feeding, parity, use of contraceptives and HRT. Blood samples were collected and tested for fasting lipid profiles, serum estrogen and progesterone. The study has revealed that high levels of serum total cholesterol (P<0.05), TAG (P<0.05), LDL-C (P<0.05) and low level of serum and HDL-C (P<0.05) were found to be associated with breast cancer. The study further reveals that blood levels of estrogen (P<0.05) and progesterone (P<0.05) were found to be lower than that of the controls. DOI: http://dx.doi.org/10.3329/bjmb.v6i2.17644 Bangladesh J Med Biochem 2013; 6(2): 58-62